Possibility of Some Indigenous Spices as Flavor Agents to Enrich Indonesia Flavor Database - Supartono, Wahyu; Guritno, Adi Djoko; Ushada, Mirwan; Sukartiko, Anggoro Cahyo (KnE Life Sciences, 2016)
Indonesia has huge potency of herbs and spices, some of them are vetiver, lime leaves and Indonesian basil. They have contribution on foods, drinks and traditional treatments. To determine their characteristics, they were distillated by boiling them with water then extracted by rotary vapor, before they were tested by Gas Chromatography – Mass Spectrometry. The essential or volatile oils detected by GS-MS depicted their specific contents and approved by Similarity Index in WILEY.LIB. Keywords: Distillation, essential oil, flavoring agent, GC-MS, herbs